Development of tea-waste impregnated with iron oxide nanoparticles for magnetic micro-solid phase extraction of non-steroidal anti-inflammatory drugs in water samples / Yagulan Muniandy - Yagulan , Muniandy (2024)
The presence of pharmaceutical compounds as well as their degradation products in the aquatic environment is of great concern. Non-steroidal anti-inflammatory drugs (NSAIDs) are one of the major pharmaceutical products that may be present in environmental water samples. In this study, a simple method based on the magnetic micro-solid phase extraction (MMSPE) technique was developed for the determination of NSAIDs in water samples prior to the UV-Vis spectrophotometer analysis. A new tea waste-impregnated with magnetic nanoparticles (MNP-TW) was successfully synthesized by the chemical co-precipitation technique. The characterization studies were carried out by Brunauer–Emmett–Teller (BET), Fourier Transform Infrared Spectroscopy (FT-IR), X-Ray Diffraction (XRD), transmission electron microscope (TEM), field emission scanning electron microscopy with energy dispersive X-ray spectroscopy (FESEM-EDX), vibrating-sample magnetometry (VSM) and thermogravimetric analysis (TGA). MNP-TW was utilized as an MSPE sorbent for the extraction and determination of ibuprofen (IBP), diclofenac (DCF) and naproxen (NAP) separately. Experimental variables affecting the extraction efficiency of NSAIDs such as sample pH, sorbent dosage, extraction time, ionic strength, the volume of sample, type of desorption solvent, desorption time and desorption volume were studied and optimized in detail. Under the optimal conditions, the calibration curves were linear for the concentration ranging between 30 and 700 μg L-1 with the coefficient of determination (R2) between 0.9964 to 0.9981. The limit of detection (LOD) was in the range from 10.30 to 11.70 μg L-1, the limit of quantification (LOQ) was in the range from 31.20 to 35.40 μg L-1 and the method exhibited excellent precision (RSD ≤ 4.83%), repeatability (RSD ≤ 4.66%) and relative recovery (86% - 115%). The green assessment was conducted, and the Analytical eco scale score obtained from this method would be 77 which shows this method is neatly a green analysis. The method presented the advantages of the study which show that the integration of MNP-TW and MMSPE with UV-Vis spectrophotometer provides a simple, sensitive, and rapid method for the extraction and determination of NSAIDs in water samples. The usage of tea waste in the extraction process presents many advantages, as it is biodegradable and versatile, and it contributes to an intelligent and sustainable economic strategy projected toward a circular economy approach.